Financial Planning and Investment Feasibility Analysis Based on Five-Year Projections Using ROI, NPV, IRR, and Financial Ratios : JEL Classification: G31, M13, L26, O16, L81 - Ridwan, Saepul; Syah , Tantri Yanuar Rahmat; Kustiawan, Unggul; Nofierni, Nofierni (Newinera Publisher, 2025)
People tend to think of financial feasibility as an issue of numbers, which it is not. It is the issue of strategic intention, capital discipline, operating structure, and expected payoff being aligned. The research proposal is a complete financial plan and investment feasibility study on a new venture in the meat supply industry using the logistic-driven process targeting HORECA in the Jabodetabek area. In a five-year financial modeling, the study analyzes the anticipated revenues, cost structure, capital demand and finance projections through Return on Investment (ROI), Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and the main financial ratios. The combination of scenario budgeting with systematic investment analysis not only builds a story of performance based on the strategic cost-allocation, liquidity maintenance and long-term solvency, but it also anticipates changing conditions, provides a clearer vision of the future by ensuring that the company can transform itself to adapt the potential improvements and counter powers to capitalize on them. Results show that profitability in the short term is sacrificed, but as of the second year, the enterprise will be able to cover its finances, achieve operational leverage, respectively high net margins as of the fifth year. The presence of a positive net present value (NPV) of 3.2 billion Indonesian rupiahs, an internal rate of returns (IRR) of 24 percent, and a 4.4-year payback indicate that as an investment it is both appealing to investors and economical in terms of capital.